HUBUNGAN PERSONAL HYGIENE DENGAN KEJADIAN SKABIES PADA MASYARAKAT PESISIR DI APUI RT 06 KELURAHAN AMPERA KECAMATAN KOTA MASOHI - Siti Fatimah Tuharea; Abuzar Wakano; Ratna Sari Rumakey (Jurnal Keperawatan Indonesia Timur (East Indonesian Nursing Journal), 2021)
Background: Scabies is a skin iritation caused by the Sarcoptes Scabies varitashominis lice which causes scabies sufferers to generally feel uncomfortable and itch . Scabies occurs due to several factors, one of which is personal hygiene. Objective: This study aims to determine the relationship between personal hygiene and the incidence of scabies in coastal communities in Apui RT 06, Ampera Village, Masohi City. Methods: This study used a descriptive analytic method with cross sectional approach. The population is 121 people. The sample in this study amounted to 55 people with purposive sampling technique. Collecting data using observation sheets and questionnaires. Data analysis used Chi-square statistical test using SPSS with a significance level of α = 0.05. Result: There were 37 (67.3%) bad personal hygiene, while 18 (32.7%) had good personal hygiene. 15 (27,3%) did not experience scabies, while 40 (72,7%) had scabies. Conclusion: From the results of the statistical test used the Chi-square test, it was found that the p-value = 0.000 <a = 0.05.